UMP denizens contributed RM16,865.85 in humanitarian aids to Somalia - UMP, PNC
Universiti Malaysia Pahang (UMP) showed that they were a generous lot when they collected RM16,865.85 for the people in Somalia who were suffering from famine and disaster.